Economic and Financial Progress in Europe, 1923-24 - Davis, Joseph S. (The Review of Economics and Statistics, 1924)
THE year I923 in Europe was one of significant, unmistakable economic progress, save only in Germany and a few minor countriesa progress slackened and modified, to be sure, by the occupation of the Ruhr and its far-reaching consequences, but nevertheless reflecting basic strength, adaptability, and accomplished readjustment which the cursory observer often overlooks or underestimates. This progress has continued in the first half of I924, a six-months period marked by provisional currency stabilization, industrial recovery, and credit stringency in Germany, the dramatic battle of the franc in France and Belgium, and the successful labors of a Committee of Experts toward a working basis for a sensible adjustment of the issues between Germany and her creditors. The present review covers most of the period of the Ruhr occupation, from January I923 to the middle of the current year. Complete statistical data, however, are not available for the second quarter of